2000
DOI: 10.1175/1520-0493(2000)128<2687:trbpal>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Precipitation and Lightning in Tropical Island Convection: A C-Band Polarimetric Radar Study

Abstract: One of the primary scientific objectives of the Maritime Continent Thunderstorm Experiment was to study cloud electrification processes in tropical island convection, in particular, the coupling between ice phase precipitation and lightning production. To accomplish this goal, a C-band polarimetric radar was deployed in the Tropics (11.6ЊS, 130.8ЊE) for the first time, accompanied by a suite of lightning measurements. Using observations of the propagation-corrected horizontal reflectivity and differential refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
174
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 196 publications
(190 citation statements)
references
References 94 publications
16
174
0
Order By: Relevance
“…Briefly, vertical profiles (250 m spacing) of radar reflectivity (Z) for every PF were processed. Ice water content (IWC, from the-5 • C level to echo top) was calculated for each vertical PR gate using an exponential size (mass, M) distribution in the form of an M -Z relationship (Carey and Rutledge, 2000): ocean (Tokay and Short, 1996) via:…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, vertical profiles (250 m spacing) of radar reflectivity (Z) for every PF were processed. Ice water content (IWC, from the-5 • C level to echo top) was calculated for each vertical PR gate using an exponential size (mass, M) distribution in the form of an M -Z relationship (Carey and Rutledge, 2000): ocean (Tokay and Short, 1996) via:…”
Section: Methodsmentioning
confidence: 99%
“…Their results indicate that the development of graupel above the freezing level is related to the overall increase/decrease in the number of cloud-to-ground (CG) flashes. Carey and Rutledge (2000) showed that CG lightning flashes were highly correlated with radar-inferred mixed-phase ice mass in time and space. Moiser et al (2011) used the radar-derived vertically integrated ice (VII) to forecast CG lightning and showed that any increase of VII over 0.42 kg m −2 is a sufficient amount of precipitation mass for cloud electrification.…”
Section: N Roberto Et Al: Multi-sensor Analysis Of Convective Activmentioning
confidence: 99%
“…The warm-rain precipitation production process dominated throughout the event, which led to accurate radar rainfall estimates. However, during the afternoon each day of the event, a small amount of lightning was observed, which suggests that a small quantity of ice was introduced into the precipitation production process (Carey and Rutledge 2000). This has the effect of lessening the performance of the tropical Z-R relationship.…”
Section: Event Overview and Radar Analysismentioning
confidence: 99%